Neonatal COVID-19 exposures and infections: a systematic review of modes of transmission, manifestations and management - Obumneme B. Ezeanosike; Dorathy C. Obu; Olapeju W. Daniyan; Onyinye U. Anyanwu; Ijeoma N Okedo-Alex; Ifeyinwa C Akamike; Edak Ezeanosike (Journal of Global Health Reports)
# Background Since the emergence of the novel coronavirus disease (COVID-19) in December 2019, several publications have emerged describing the manifestations of the disease in different age groups. Reports from the newborn group have however been sparse. This review summarizes the mode of transmission, clinical presentations as well as treatment and outcomes of COVID-19 in neonates.